Comparison between Outcomes of Open and Arthroscopic Fixation of Tibial Spine Avulsion Fractures - Muhammad Amir Sohail; Amna Bashir; Mahnoor Amjad; Muhammad Bilal Afzal; Javed Hassan Raza (Gandhara University, 2024)
OBJECTIVES This study aimed to compare the functional outcomes of fragment reduction and to measure the rate of postoperative complications between arthrotomy (ORIF) and arthroscopy(ARIF) pediatric tibial spine avulsion fractures using the Lysholm knee scoring system (limp, pain swelling, climbing stairs) and IKDC subjective knee evaluation form. METHODS: This Comparative Study was conducted at the Department of Orthopedic Surgery, Jinnah Hospital Lahore, between 2021-2022. A total of 42 patients who had tibial spine avulsion fracture with follow-up of 6 months were included. Twenty-one patients were treated with ORIF, and 21 were treated with ARIF. Functional outcomes were assessed using the IKDC score and LYSHOLM score (Follow-up rate was 95 %). Radiographic findings of patients were recorded, and a statistical study was done. The level of significance was set at <0.05. RESULTS: The study revealed that out of 42 Participants, 36(85.71%) males and 6 (14.29 %) females participated in the survey with the age range of 8-16 years with a mean age of 12.02± (2.53) years. Out of 42 Participants, 22 (52.4%) had motor vehicle accidents with type 3(38.1%) and 4(54.8%) modified Meyers and Mckeever fracture classification. At the end of the follow-up period, the mean IKDC score was 90.52 + 1.50 (p = 0.00, CI = 95%). The Lysholm score was 90.676.11 compared to the last follow-up (p=0.20, CI = 95%). Compared to ORIF, only 5(11.9%) patients complained of post-op infection or vascular injury. CONCLUSION: This study observed better functional outcomes in arthroscopic reduction and immobilization than in open reduction internal fixation. Arthroscopy for TSAF decreases the risk of arthrofibrosis and minimizes morbidities and better management of symptoms. Compared to OIRF, ARIF showed good content validity for the IKDC and Lysholm scales.